PENGARUH PENDAPATAN PESERTA BPJS KESEHATAN MANDIRI TERHADAP PEMANFAATAN JAMINAN KESEHATAN NASI - Syamsuddin, Nella Tri Surya; Kur’aini, Sri Nurul (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2022)
The utilization of national health insurance in the public house service of Nene Mallomo, Sidenreng Rappang Regency has greatly increased with the number of daily visits increasing, but the coverage of BPJS membership is still very low compared to all districts in South Sulawesi Province. The type of this research is quantitative with a Cross-Sectional Study approach. The population in this study were all participants of BPJS Kesehatan Mandiri, Sidenreng Rappang Regency who used health services at the Nene Mallomo Hospital, as many as 48,033 people. The sampling technique in this study is a purposive sampling technique with a sample size of 100 respondents. The data analysis performed was univariate and bivariate using the chi-square test. The results of the chi-square test indicate that there is an influence between knowledge (p = 0.000) and income (p = 0.000) on the national health insurance (JKN) for independent BPJS Health participants in services at the Nene Mallomo general hospital, Sidenreng Rappang Regency. It is concluded that knowledge and income affect the use of national health insurance, and it is hoped that the community will register to become BPJS Health participants and take advantage of the national health insurance in health services, both at puskesmas and hospitals, especially at the Nene Mallomo general hospital, Sidenreng Rappang Regency.